#TITLE_ALTERNATIVE# - ZAHRINA WULANSARI (NIM : 12911019), NADIA
The goal of this study is to analyze the characteristics of Rossby waves in the Southeastern Tropical Indian Ocean (SETIO) during 1993 to 2012 using data sea surface height anomaly (SSHA) from satellite altimetry TOPEX/Poseidon. The data will be displayed in the diagram HovmÃƒÂ¶ller, while the characteristic of that waves will be shown using 2D frequency-wavenumber spectral analysis. The results show that the Rossby waves at 10oLS have a quasi-biennial and interannual variation (1.6 to 3.2 years) with the phase velocity and wavelength ranging from 6.3 to 6.5 cm/s and 3213 to 6594 km. These waves is assumed come from the reflected Kelvin waves at Sumbawa island. In addition, the Rossby waves in 12oLS and 13oLS has interannual variation (5.8 to 6.8 years) with phase velocity ranged from 3.8 to 4.5 cm /s. It is assumed comes from the Pacific Ocean. While Rossby waves in 15oLS have quasi-biennial variation with the phase velocity about 2.76 cm/ s and wavelength ranging from 1415 - 1464 km. This Rossby waves is indicated formed by the wind.